Coping behaviors of first-generation college students across family structures - Tangco-Siason, Amabel (Frontiers in Education, 2025)
IntroductionThis study investigated the coping behaviors of 2,236 first-generation college students in the province of Iloilo, Philippines, focusing on how these learners manage academic, emotional, and socio-economic stressors through various strategies.MethodsAn embedded mixed-methods design was employed to gather both quantitative and qualitative data. The quantitative phase involved the administration of a coping behavior scale to 2,236 participants to determine patterns and variations in coping levels. The qualitative phase complemented this with in-depth interviews among nine purposively selected first-generation students, providing a richer understanding of their personal experiences and adaptive strategies. This combination allowed for the convergence of statistical findings with narrative insights.ResultsThe quantitative results revealed a generally high level of coping among the respondents, with cognitive reappraisal (M = 3.01, SD = 0.61), spiritual support, and relaxation emerging as the most frequently utilized strategies. In contrast, social support and self-expression were only moderately practiced, indicating a tendency toward internalized coping mechanisms. High coping levels were consistent across sex, birth order, and income levels, though students from intact families reported greater use of social support, highlighting the influence of family structure. While there was no significant difference in the overall coping behaviors of the students, a significant relationship was observed among those from families experiencing disruption in relation to their birth order (ρ = −0.04, p = 0.19).DiscussionThe qualitative findings produced six major themes that deepened the quantitative results: (1) Weight of Familial Expectations and Financial Strain, (2) Coping Through Spiritual Anchoring, (3) Cognitive and Emotional Self-Regulation, (4) Selective Use of Social Support, (5) Birth Order and Coping Responsibility, and (6) Navigating Academic Overload and Emotional Fatigue. These themes illustrated the students’ adaptive behaviors rooted in cultural values, personal determination, and spiritual beliefs. Moreover, the findings revealed a multidimensional stress landscape among first-generation college students, underscoring their psychological resilience and strong reliance on spirituality, inner strength, and culturally embedded values. The integration of quantitative and qualitative data suggests that while these students experience multiple stressors, they exhibit adaptive and resourceful coping patterns. The study concludes by emphasizing the need for inclusive and context-sensitive psychosocial programs in higher education institutions that recognize and strengthen the coping resources of first-generation learners.